Colonoscopy for colonic wall thickening at computed tomography: a worthwhile pursuit? - Nicholson, B; Hyland, R; Rembacken, B; Denyer, M; Hull, M; Tolan, D (2011)
BACKGROUND: In the absence of official guidance for the management of colonic wall thickening identified by computed tomography (CT), a common clinical dilemma surrounds the volume of colonoscopies subsequently performed. METHODS: To identify whether colonic wall thickening identified at CT consistently warrants colonoscopy, consecutive colonoscopies performed at Leeds Teaching Hospitals Trust in 2008 and recorded as "possible colonic lesion on cross-sectional abdominal CT" in an endoscopic database were retrospectively analyzed. Clinical, radiologic, colonoscopic, and histologic data were obtained from medical records. RESULTS: Of 4,702 colonoscopies, 94 (2%) had a full data set meeting the inclusion criteria. The primary diagnoses were normal condition (n = 11, 11.7%), adenocarcinoma (n = 25, 26.6%), adenoma (n = 23, 24.5%), diverticular disease (n = 12, 12.8%), nonspecific colitis (n = 6, 6.4%), Crohn's disease (n = 4, 4.3%), and hyperplastic polyp (n = 3, 3.2%). Computed tomography and colonoscopy were concordant for specific pathology in 79.8% of the cases (n = 75). Compared with diagnosis after histology, colonoscopy alone correctly identified specific pathology in 18.1% of the cases (n = 17), and CT alone was correct in 4.3% of the cases (n = 4)), whereas both were incorrect in 3.2% of the cases (n = 3). Computed tomography had a sensitivity of 72.3% (95% confidence interval [95% CI], 61.9-80.8%), a specificity of 96.5% (95% CI, 94.9-97.6%), a positive predictive value of 72.3%, and a negative predictive value of 96.5%. In 63.8% of the cases (n = 60), CT identified pathology necessitating further intervention at the time of colonoscopy or afterward, and in 28.7% of the cases (n = 27), CT identified pathology requiring no additional intervention. In the remaining 7.4% of the cases (n = 7), CT detected no new pathology. CONCLUSION: Computed tomography is highly predictive of colonic pathology compared with final outcome after colonoscopy and biopsy. For patients without a pre-existing diagnosis, colonic wall thickening demonstrated at CT warrants further investigation with colonoscopy.